2007
DOI: 10.1063/1.2712437
|View full text |Cite
|
Sign up to set email alerts
|

Bosonic helium droplets with cationic impurities: Onset of electrostriction and snowball effects from quantum calculations

Abstract: Variational MonteCarlo and Diffusion MonteCarlo calculations have been carried out for cations like Li + , Na + and K + as dopants of small helium clusters over a range of cluster sizes up to about 12 solvent atoms.The interaction has been modelled through a sum-of-potential picture that disregards higher order effects beyond atom-atom and atom-ion contributions. The latter were obtained from highly correlated ab-initio calculations over a broad range of interatomic distances.This study focuses on two of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 37 publications
5
60
1
Order By: Relevance
“…Most theoretical studies of cations solvated in helium concluded that the solid-like structure does not extend beyond the first shell; atoms in the second shell are more delocalized and liquid-like. Gianturco and co-workers 33,34 employed the variational Monte Carlo method and ab initio potential energy curves to optimize a trial wave function; in a second step, they applied the diffusion Monte Carlo algorithm in order to obtain the energy and the geometric distributions of the cluster. They found a rigid solvation shell of icosahedral symmetry for He 12 Na + , but delocalization in the first shell increases if the number of helium atoms is smaller or larger than 12.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most theoretical studies of cations solvated in helium concluded that the solid-like structure does not extend beyond the first shell; atoms in the second shell are more delocalized and liquid-like. Gianturco and co-workers 33,34 employed the variational Monte Carlo method and ab initio potential energy curves to optimize a trial wave function; in a second step, they applied the diffusion Monte Carlo algorithm in order to obtain the energy and the geometric distributions of the cluster. They found a rigid solvation shell of icosahedral symmetry for He 12 Na + , but delocalization in the first shell increases if the number of helium atoms is smaller or larger than 12.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, early experimental work suggested that no more than two shells are part of the snowball, 2 and many recent theoretical studies of ions solvated in helium concluded that no structural order exists outside of the first solvation shell. 33,34 Even in the first layer, quantum effects may destroy structural order and wash out shell effects. 31,3537 We note that these theoretical studies included quantum effects (zero-point motion and the bosonic nature of helium) to various degrees, which explains some of the differences between them.…”
Section: Introductionmentioning
confidence: 99%
“…By subsequently adding He atoms to the ion and computing the resulting cluster structure, marked differences in the Ak + He N geometry depending on N are found [13]. The first solvation shell consists of equivalently arranged He atoms, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The geometric structure of He shells in alkali-ion doped clusters was studied by quantum variational and diffusion Monte Carlo calculations [12,13,14]. By subsequently adding He atoms to the ion and computing the resulting cluster structure, marked differences in the Ak + He N geometry depending on N are found [13].…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39], for instance) and we therefore present here only a brief outline of it. It is formed by a pure variational Monte Carlo (VMC) calculation followed by a diffusion Monte Carlo (DMC) approach.…”
Section: Quantum Monte Carlo Methodsmentioning
confidence: 99%